Pro iOS table views for iPhone, iPad, and iPod touch - Duckett, Tim (Apress, 2012)
If you're an iOS app developer, chances are you'll be using table views in your development projects. Table views are the bread and butter of iOS apps. With them, you can create everything from the simplest of lists to fully tricked-out user interfaces. Table views are also one of the most complex components found in UIKit. While using them for boring standard user interfaces is quite simple, customizing them can become really challenging. Pro iOS Table Views takes a task-oriented focus to assist you when implementing customized table views. Although it delves deeply into the Table View API, you can always decide in which level of detail you want to dive in. It's aimed to be a great reference and customization cookbook at the same time, useful for beginners as well as intermediate developers. Covers the entire Table View API in depth Covers customization and performance topics in depth Task-oriented reference with multiple levels of detail Note: source code for this title is currently available for download at: https://github.com/timd/Pro-iOS-TableViews.